Life beside bars: confinement and capital in an American prison town - Pearson, Heath Dorset (Duke University Press, 2024)
"In Life beside Bars, heath pearson showcases dynamic, interdependent community as the best hope for undoing the systems of confinement that reproduce capital in Cumberland County, New Jersey-a place that is home to three state prisons, one federal prison, and the regional jail. Pearson places today's prisons within the region's longer history of Lenape genocide, chattel slavery, Japanese American labor camps, and other forms of racialized punishment and carceral control. From this vantage, prisons appear not as the structural fix for the region's failed political economy, but as a continuation of the carceral principle that has always sustained it. This ongoing use of confinement, though, is merely the backdrop. Through ethnographic vignettes written in story form, pearson offers an alternative history of the unruly and unexpected ways that people resist, get by, make money, find joy, and build radical social life in the small, unseen spaces beside large-scale confinement. As such, pearson enriches our understanding of daily life in and around prisons-in any American community-while providing a kaleidoscope of possibilities for theorizing and organizing alternative paths"--